The Effect of Product Quality, Price and Product Design on Purchasing Decisions of Sasword Disutoru Products - Rizal Syaiful; Mudji Astuti (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the Effect of Product Quality, Price and Product Design on Purchasing Decisions. The object of research is Sasut Disutoru in Sidoarjo. The sample collection method uses non probability sampling and obtained 100 respondents using incidental sampling techniques. The research approach uses a quantitative approach and data analysis tools using multiple linear regression with SPSS version 18 application. Research results obtained from the validity test on all statements of the questionnaire are said to be valid. For the reliability test of all the variables obtained by Cronbach alpha> 0.5 and declared reliable. Furthermore, based on the F test (simultaneous) shows that simultaneously the Store Atmosphere and Service Quality variables on the Purchase Decision is 0.001. Then based on the results of the t test (partial) showed that the Store Atmosphere variable partially had a significant positive effect on the Purchasing Decision of 0.023 <0.05. And Service Quality variable partially has a significant positive effect on Purchasing Decisions of 0.012 <0.05.